On the spore formation process in actinomycetes - LOCCI, ROMANO; PETROLINIBALDAN, BRUNA (Gjornâl Furlan des Siencis - Friulian Journal of Science, 2010)
Details of Streptoverticillium structures as detected by scanning electron microscopy are illustrated. The development of species belonging to the genus has been followed from germination to spore production. Sporulating features of pseudoverticillate cultures have also been observed. The peculiar characteristics of spore formation, which includes an initial twisting of the sporulating hypha, are documented.